Enhancing Educational Quality: The Role of Principal Instructional Leadership in Senior High Schools - Delissa Apriliyanti; Akil; Achmad Taufik Ismail (Journal of Educational Management Research, 2026)
This study aims to analyze the instructional leadership strategies employed by school principals in managing learning programs during the transition from the 2013 Curriculum to the Merdeka Curriculum. A qualitative case study approach was used to explore leadership practices in depth. Data were collected through semi-structured interviews with the principal, the vice principal for curriculum affairs, and subject teachers. Informants were selected using snowball sampling, while data validity was ensured through source and method triangulation. The findings reveal that the principal implemented three key instructional leadership strategies based on Hallinger’s model: establishing and communicating clear school goals, managing curriculum implementation effectively, and fostering a positive school climate. These strategies helped maintain the stability of instructional quality throughout the curriculum transition process. In addition, the implementation of these strategies was associated with a significant increase in student admissions through the National Achievement-Based Selection pathway, rising from 9 to 36 students. The study implies that effective instructional leadership plays a crucial role in supporting curriculum change, reducing implementation challenges, and sustaining educational quality during periods of policy transition. School leaders are therefore encouraged to strengthen strategic planning, curriculum management, and collaborative school cultures to ensure successful curriculum implementation.